Juridical review of cases of human rights violations against the Uighur Ethnic and its resolution mechanisms in the perspective of international law - Rangga Suganda; Wita Setyaningrum (Universitas Muhammadiyah Magelang, 2023)
Human Rights Violation is the act of individuals or groups, including state authorities, who intentionally or unintentionally disregard, restrict, or revoke human rights. Human rights violations committed by the Chinese government against ethnic Uighurs are also occurring in Xinjiang. The presence of human rights violations in Xinjiang is an attempt by the Chinese government to eradicate the Uighur ethnic group's indigenous culture. Also deemed to be rebels, Uighurs have joined international terrorist networks. Consequently, the Chinese government has implemented several actions and policies that are classified as violations of human rights. This study discusses two main issues, namely how cases of violations and crimes against humanity in Xinjiang in the perspective of international law and how the mechanism of settlement of human rights violations that have occurred through the perspective of international law. This research is normative legal research, the sources used are primary, secondary, and tertiary legal materials. The data collection technique is carried out using a literature study technique, and data analysis will be carried out using a normative juridical approach or seeing the law as the norm in society. The results of this study are that among these policies have led to several violations of human rights, ranging from violations of civil and political rights, crimes against humanity, economic discrimination, social, and cultural, to human rights violations against women and children. For this reason, it is very necessary to resolve human rights violations in Xinjiang through international legal instruments, namely the United Nations Charter and the 1998 Rome Statute. Steps that can be taken to resolve human rights violations in Xinjiang are through peaceful resolution of the conflict or through international courts.